Theta: Rapid installation and acceptance of an XC40 KNL system. (26th September 2017) - Harms, Kevin; Leggett, Ti; Allen, Ben; Coghlan, Susan; Fahey, Mark; Holohan, Carissa; McPheeters, Gordon; Rich, Paul
Summary: In order to provide a stepping stone from the Argonne Leadership Computing Facility's (ALCF) world class production 10 petaFLOP IBM BlueGene/Q system, Mira, to its next generation 200 petaFLOPS 3rd generation Intel Xeon Phi system, Aurora, ALCF worked with Intel and Cray to acquire an 8.6 petaFLOPS 2nd generation Intel Xeon Phi–based system named Theta. Theta was delivered, installed, integrated, and accepted on an aggressive schedule in just over 3 months. We will detail how we were able to successfully meet the aggressive deadline as well as lessons learned during the process.